2017
DOI: 10.3926/ic.1119
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing purchase intention towards consumer-to-consumer e-commerce

Abstract: Purpose: This study explores factors that influence consumer's purchase intention at three consumer-to-consumer (C2C) e-commerce companies in Indonesia. Originality/value: This study represents purchase intention in the consumer-to-consumer ecommerce by investigating three case study using technology acceptance model as a guiding theory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
67
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(103 citation statements)
references
References 21 publications
5
67
0
7
Order By: Relevance
“…The participants' use intentions on Laundry X are the ease of use, fast response, trustworthiness, reliable, and experience. These findings are in line with prior studies [11][12][13][32][33][34][35] which motivated them to patronize the same online laundry provider, Laundry X. Due to high satisfaction with the Laundry X service, they likely to repeat their use while spread the good news about Laundry X to others.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The participants' use intentions on Laundry X are the ease of use, fast response, trustworthiness, reliable, and experience. These findings are in line with prior studies [11][12][13][32][33][34][35] which motivated them to patronize the same online laundry provider, Laundry X. Due to high satisfaction with the Laundry X service, they likely to repeat their use while spread the good news about Laundry X to others.…”
Section: Discussionsupporting
confidence: 88%
“…Their empirical finding came from 370 survey was that both transaction related service and prepurchase service were comes from navigation experience. More recent research in 2017 comes from Indonesia [35] about factors that influence consumer's purchase intention at three consumer-toconsumer (C2C) e-commerce companies in Indonesia. Quantitative method was used and found that trust and risk are found to be significantly affecting purchase intention in Company A.…”
Section: Service Quality and Purchase Intentionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on e-commerce topics were generally more towards online buyers (Iqbal et al 2012;Shalini andHemamalini 2015, andDachyar andBanjarnahor 2017) or the adoption of e-commerce in MSMEs (Savrul et al 2014, Rahayu and John Day 2015, Venkatesh and Kumari 2015and Ueasangkomsate 2015. Studies on e-commerce topics related to intention theory generally applied TAM (Lesmono 2015, Jamshidi and Hussin 2016, Dachyar and Banjarnahor 2017and Natarajan et al 2017 whereas the study of credit applying intention theory usually applied TPB (Abdullah and Wahab 2015, Makpotche et al 2015, Brizi et al 2016, Kajenthiran et al2016and Tolba et al 2016).…”
Section: Introductionmentioning
confidence: 89%
“…There are studies that try to enhance ecommerce with various strategies such as to give compensation in automated models, (Shojaiemehr & Rafsanjani, 2018). In the same context, there are studies such as transaction security verification (Yu, Ding, Liu, Wang, & Crossley, 2018); logistics analysis and supply chain management (Yu, Wang, Zhong, & Huang, 2017), (Pei & Yan, 2019); study of activities to balance supply and demand (Gölgecia, Karakasb, & Tatogluc, 2018); price prediction (Tseng, Lin, Zhou, Kurniajaya, & Li, 2018); sales prediction (Yuan, Xu, Li, & Lau, 2018); purchasing prediction (Dong & Jiang, 2019); analysis of purchase intention (Dachyar & Banjarnahor, 2017), (Ramiŕez-Correa, Grandón, & Arenas-Gaitań, 2019), (Li, Feng, & Zhai, 2019); customer loss prediction (Berger & Kompan, 2019); analysis of elements to attract and retain customers (Choshin & Ghaffari, 2017), (Deng & Gao, 2018), (Jannach, Ludewig, & Lerche, 2017), (Wu, Zhang, Tian, & Wu, 2019), (Chen, 2019); trust analysis (Kim & Peterson, 2017), (Sánchez-Alzate & Montoya Restrepo, 2017), (Masseya, Wanga, & Kyngdon, 2019); etc. This work takes the e-commerce strategy as a marketing strategy because the arguments showed are more general This paper is organized as follow: In the next section, fundamental consideration theoretical is presented about satisfaction grade and some related concepts are also included.…”
Section: Introductionmentioning
confidence: 99%